Біопротекторна дія цинку в макро- і наноаквахелатній формі на ембріогенез щурів за умови свинцевої інтоксикації - V. G. Kaplunenko; N. M. Onul; I. S. Chekman; E. M. Beletskaya; V. P. Stus (Medičnì Perspektivi, 2013)
The article presents results of studied influence of low doses of lead and zinc (nanozinc) on embryonal development in a laboratory experiment on rats.  Negative influence of lead on pregnancy of laboratory animals, manifested in violation of the physiological dynamics of the rectal temperature and decrease in body weight gain was revealed. Embryotoxic effect of low doses of lead results in increased fetal mortality by 2.16 times compared to the control group of animals, deterioration of the morphometric indices of fetuses, violation of placentogenesis. Simultaneous injections of zinc on background of lead intoxication causes a protective effect on the body of pregnant rats and embryonal development of the offspring, more pronounced for zinc citrate, received by using aquananotehnology, as compared to zinc chloride. Thus, by morphometry indices, male fetuses were more sensitive to prenatal lead exposure in comparison to female fetuses.